Analysis of the Impact of Mineral and Coal Downstreaming Policy on Global and National Economies: A GTAP Approach - Basuki Rahmad Saleh; Irdam Ahmad; Herlina Juni Risma Saragih; Agus Adriyanto; Susanna Renna Ertanti (Borong Newinera Publisher, 2026)
Indonesia's mineral and coal downstreaming policy, which imposes export bans and restrictions on raw minerals such as nickel, bauxite, copper, and coal, represents one of the most ambitious resource industrialization strategies globally. This study aims to analyze the potential and impact of the mineral and coal downstreaming policy on Indonesia's macroeconomic and sectoral economic indicators as well as its implications for global trading partners. The analysis method employs the GTAP (Global Trade Analysis Project) version 10 database model with two cooperation scenario approaches: a 50% reduction in raw mineral exports (Simulation 1) and a 95% reduction in raw mineral exports (Simulation 2). The macroeconomic indicators analyzed include welfare (equivalent variation), real Gross Domestic Product (GDP), household consumption, government expenditure, investment, exports, imports, and trade balance. The sectoral indicators include output changes and employment opportunities. The results show that Indonesia's downstreaming policy promotes an increase in real GDP, household welfare, domestic consumption, and investment, with the highest gains occurring in the nickel processing, ferronickel, and manufactured metals sectors. However, the policy creates a temporary trade balance deterioration due to increased capital goods imports for smelting infrastructure. From the sectoral perspective, downstream mineral industries particularly ferronickel, chemical fertilizers derived from coal gasification, and mineral-based manufactured goods record the highest output and employment increases. These findings underscore the strategic importance of accelerating hilirisasi policies while mitigating trade risks through market diversification.